Tumor-resident adenosine-producing mesenchymal stem cells as a potential target for cancer treatment - Arab, Samaneh; Alizadeh, Akram; Asgharzade, Samira (Clinical and experimental medicine, 2021)
The development of new therapies based on tumor biology is one of the main topics in cancer treatment. In this regard, investigating the microenvironment and cellular composition of the tumor is of particular interest. Mesenchymal stem cells (MSCs) are a major group of cells in the tumor tissue and play a critical role in tumor growth and development. Investigating the mechanisms by which MSCs influence tumor growth and progression is very useful in establishing new therapeutic approaches. MSCs have some immunological capacities, including anti-inflammatory, immune-regulatory, and immune-suppressive abilities, which help the tumor growth in the inflammatory condition. They can suppress the proliferation and activation of CD4 + T cells and direct them toward the regulatory phenotype through the release of some factors such as indoleamine 2,3-dioxygenase, prostaglandin E2, and HO-1, PD-1 ligands (PD-L1 and PD-L2) and promote tolerance and apoptosis. Besides, these cells are able to produce adenosine. Adenosine has a key role in controlling the immune system by signaling through receptors located on the surface of immune cells. It plays a very essential role in tumor growth and progression. In the present review, we investigate and introduce adenosine-producing mesenchymal stem cells as a potential target for cancer treatment.